2019
DOI: 10.3390/nu11040899
|View full text |Cite
|
Sign up to set email alerts
|

Uncontrolled Eating during Pregnancy Predicts Fetal Growth: The Healthy Mom Zone Trial

Abstract: Excess maternal weight gain during pregnancy elevates infants’ risk for macrosomia and early-onset obesity. Eating behavior is also related to weight gain, but the relationship to fetal growth is unclear. We examined whether Healthy Mom Zone, an individually tailored, adaptive gestational weight gain intervention, and maternal eating behaviors affected fetal growth in pregnant women (n = 27) with a BMI > 24. At study enrollment (6–13 weeks gestation) and monthly thereafter, the Three-Factor Eating Questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 64 publications
(84 reference statements)
0
8
1
Order By: Relevance
“…Uncontrolled eating has been associated with higher caloric intake [32]. Also, uncontrolled eating during pregnancy predicts faster fetus growth, a risk of macrosomia (large baby for the gestational age) [43]. Prior research has reported the link between uncontrolled eating and obesity in low-income postpartum women with all body sizes [25], which is contradictory to our finding.…”
Section: Discussioncontrasting
confidence: 99%
“…Uncontrolled eating has been associated with higher caloric intake [32]. Also, uncontrolled eating during pregnancy predicts faster fetus growth, a risk of macrosomia (large baby for the gestational age) [43]. Prior research has reported the link between uncontrolled eating and obesity in low-income postpartum women with all body sizes [25], which is contradictory to our finding.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, 110 study authors were contacted for unpublished data. Among them, 12 provided study data [40][41][42][43][56][57][58][59][60][61][62][63][64][65]. In total, this systematic review included 20 RCTs [40-43, 45-52, 56-63], of which 19 were synthesized in meta-analyses.…”
Section: Study Selectionmentioning
confidence: 99%
“…The 17 individually- [41, 42, 45-52, 56-60, 62, 63] and three cluster-RCTs [40,43,61] contributed data of 11, 385 randomized participants from 11 different countries (Table 1). Sample sizes at randomization ranged from 31 to 2286 participants [43,60]. Children were followed-up from 1 month to 7 years postpartum.…”
Section: Study and Population Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is an important area for future research to consider as it is as yet unknown if maternal stress-induced alterations in ghrelin concentrations translate to unhealthy eating patterns and reduced diet quality in pregnant women, which in turn could influence pregnancy outcomes. For example, emerging evidence suggests that emotional or disinhibited eating behaviors may be associated with excess gestational weight gain (Blau et al, 2018) and rapid fetal growth (Savage et al, 2019), although this is an area of research requiring further investigation.…”
Section: Tablementioning
confidence: 99%